Refined expression quantitative trait locus analysis on adenocarcinoma at the gastroesophageal junction reveals susceptibility and prognostic markers - Zhong, Ce; Wu, Chen; Lin, Yuan; Lin, Dongxin (Frontiers in Genetics, 2023)
Objectives: This study aimed to explore cell type-level expression quantitative trait locus (eQTL) in adenocarcinoma at the gastroesophageal junction (ACGEJ), identify susceptibility and prognosis markers. Methods: Whole-genome sequencing (WGS) was performed on 120 paired samples from Chinese ACGEJ patients. Germline mutations were detected by gatk-tools. RNA sequencing (RNA-seq) data of ACGEJ samples from our previous studies. Public single-cell RNA sequencing (scRNA-seq) data was used to produce proportion of epithelial cells. MatrixEQTL and a linear mixed model was used to identify condition-specific cis-eQTLs. R package coloc was used to perform co-localization analysis with public data of genome-wide association studies (GWASs). Log-rank and Cox regression test were used to identify survival-associated eQTL and genes. Functions of candidate risk loci were explored by experimental validation. Results: Refined eQTL analysis of paired ACGEJ samples was performed and totally 2,036 potential ACGEJ-specific eQTLs with East Asian specificity were identified. ACGEJ-gain eQTLs were enriched at promoter regions more than ACGEJ-loss eQTLs. rs658524 was identified as top eQTL close to transcription start site of its paired gene (CTSW). rs2240191 - RASAL1, rs4236599 - FOXP2, rs4947311 - PSORS1C1, rs13134812 - LOC391674 and rs17508585 - CDK13-DT were identified as ACGEJ-specific susceptibility eQTLs. rs309483 - LINC01355 was associated with overall survival of ACGEJ patients. We explored functions of candidate eQTLs including rs658524, rs309483, rs2240191 and rs4947311 by experimental validation. Conclusions: This study provides new risk loci for ACGEJ susceptibility and effective disease prognosis biomarkers.